Getting Europe back to work. Crisis (re)production and crisis overcoming in Europe - Redakcja (Adam Mickiewicz University in Poznań, 2019)
The aim of this publication is to discuss the current determinants generating economic growth in the European Union, which is still a challenge in the post-crisis context. It has been investigated globally, continentally and regionally. At the same time, the key question is whether this economic growth is compatible with the social dimension and social values, which is one of the main considerations of young Europeans, who were most adversely affected by the crisis.
Keywords: social Europe; economic crisis; European integration; young Europeans